Binary Combination of Carica papaya, Areca catechu and Myristica fragrans with Piperonyl Butoxide / MGK-264 against Freshwater Snail Lymnaea acuminata - Farhat Hanif; Dinesh Kumar Singh (Tropical Life Sciences Research, 2013)
Piperonyl butoxide (PB) and MGK-264 were used to enhance the toxicity of the active components papain, arecoline and myristicin from the plants Carica papaya, Areca catechu and Myristica fragrans, respectively, against the vector snail Lymnaea acuminata. A time- and dose-dependent relationship was observed for the toxicity of these combinations. The toxic effects of these plant-derived molluscicides in combination with the synergists PB and MGK-264 were several times higher than the effect of the individual treatments. The highest degree of synergism was observed when MGK-264 was used in combination with C. papaya latex (10.47-fold increase) and PB was used with papain (8.35-fold increase). Piperonil butoksida (PB) dan MGK-264 telah digunakan untuk mempertingkatkan ketoksikan komponen aktif iaitu papain, arekolina dan miristisin, masing-masing daripada tumbuhan Carica papaya, Areca catechu dan Myristica fragrans, terhadap siput vector Lymnaea acuminata. Suatu perhubungan bersandar masa dan dos telah diperhatikan untuk ketoksikan kombinasi-kombinasi ini. Kesan toksik molusisida daripada tumbuhan-tumbuhan ini dengan kombinasi synergis PB dan MGK-264 didapati lebih tinggi daripada kesan rawatan tanpa kombinasi. Synergism tahap paling tinggi diperhatikan apabila MGK-264 telah digunakan dengan kombinasi lateks C. papaya (penambahan 10.47 kali) dan PB dengan papain (penambahan 8.5 kali).